Pengukuran suhu, pH dan kadar substrat terhadap aktivitas enzim Galactose-1-Phosphate Uridyltransferase - Sisca, Sisca; Parwanto, Edy; Hartanti, Monica Dwi; Tjahyadi, David (CV. Publikasi Indonesia, 2024)
Galactose-1-phosphate uridyltransferase (GALT) is an important enzyme involved in galactose metabolism. Understanding the factors influencing GALT activity is critical to elucidate its physiological role and potential therapeutic implications in galactosemia. In developing new drugs, chicken intestine/liver powder can be used as an enzyme source, GALT, to treat galactosemia. Therefore, it is necessary to research the characterization of the GALT enzyme in chicken intestine and liver powder. In this study, we investigated the influence of temperature, pH, and substrate level on GALT enzyme activity using an experimental approach in vitro. The optimum pH extraction results show that the optimum pH for the extraction of the chicken intestine and liver GALT is pH 7, with activity values ​​of 0.47 units/mL and 0.3953 units/mL, respectively. The optimum temperature for the extraction of chicken intestine and liver GALT is 37℃ with substrate hydrolysis capabilities of 0.48 U/mL and 0.57 U/mL, respectively. Meanwhile, the optimum substrate content is 400x. These insights provide a valuable foundation for further research aimed at comprehensively understanding GALT function, developing targeted interventions for disorders of galactose metabolism, and possible application in the development of new drugs for galactosemia